Virtual Intraoperative Cholangiogram Using WebCL - YU, Alexander (Stud Health Technol Inform, 2016)
In this paper, we propose a Virtual Intraoperative Cholangiogram (VIC) training platform. Intraoperative Cholangiogram (IC) is an imaging technique of biliary anatomy with using fluorescent fluids sensitive to the X-Rays. The procedure is often employed to diagnose the difficult cases such as abnormal anatomy or choledocholithiasis during the laparoscopic cholecystectomy. The major challenge in cholangiogram is accurate interpretation of the X-Ray image, which requires extensive case training. However, the training platforms that support generation of various IC cases have been lacking. In this study, we developed a web based platform to generate IC images from any virtual bile duct anatomy. As the generation of X-Ray image from 3D scene is a computationally intensive task, we utilized WebCL technology to parallelize the computation for achieving real-time rates. In this work, we present details of our WebCL IC generation algorithm and benchmark results.